Comparison of Static and Active Downforce on Corn at the Kansas River Valley Experiment Field in 2020 - E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2021)
Uniformity of plant spacing and emergence have been shown to be significant contributing factors to increasing corn yields. Improved seed meters that offer very precise seed drop have been available on planters for a number of years. However, uniformity in plant emergence continues to be a challenge, especially with reduction of tillage and in fields with variable soils. Correct, consistent depth is critical for uniform corn emergence. By keeping the gauge wheels on the ground, consistent depth is achieved. An active downforce system, such as Precision Planting’s DeltaForce, applies hydraulic downforce or lift to the row unit. With a Precision 20|20 planter monitor, load sensor readings of the downforce on the gauge wheels can be monitored and the target pressure adjusted from the monitor. The 20|20 display detects the load cell readings and adjusts the applied downforce or lift to maintain the gauge wheels’ contact with the ground while also preventing compaction beyond what is necessary for creating a good furrow.
Keywords: planter downforce; corn; active downforce; static downforce